Effectiveness of STEM Learning Model and Project-Based Learning to Enhance Critical Thinking Skills in Senior High School - Budhyawan S. Bandjar; Mohammad Gamal Rindarjono; Singgih Prihadi (JAMBURA GEO EDUCATION JOURNAL, 2024)
STEM and Project-Based Learning (PjBL) learning models have been applied to support 21st century learning. However, no empirical evidence has been found to reveal the combined effectiveness of the two models. This study aims to determine the effectiveness of STEM, Project-Based Learning (PjBL), and lecture learning models in improving critical thinking skills. The research was conducted at SMA Negeri 8 Ternate City, North Maluku Province, involving 64 students divided into three classes studying Indonesian natural resource management. A concurrent embedded strategy combining quantitative and qualitative data collection was used. Initial test data indicated reliability at 0.76, with normality tests for the STEM model at 0.08, the PjBL model at 0.13, and lecture learning at 0.14, all showing normally distributed data. The homogeneity test showed homogeneous data with a value of 1.097. The balance test using one-way ANOVA indicated balanced initial abilities (Fhitung 2.52 Ftabel 3.14). Results demonstrated that by applying the STEM and PjBL learning models, students achieved proficiency in critical thinking skills. Final test data, including normality tests, one-way unequal ANOVA, and post-ANOVA tests, showed significant improvement in critical thinking skills. The STEM model and PjBL model were both effective with no significant differences between them, while both differed significantly from the lecture learning model. The results suggest that both STEM and PjBL models are effective in enhancing critical thinking skills. To address the shortcomings of traditional lecture methods, educators should consider integrating STEM and PjBL approaches into their teaching practices.